Anal ultrasound in patient with leukoplakia of the anal canal - Sudoł-Szopińska, Iwona (Radiology and oncology (Ljubljana), 2002)
Background. Leukoplakia is considered to increase the risk of development of anal carcinoma. We present a case of leucoplakia which underwent a malignant transformation and usefulness of the anal endosonography (AES) in the assessment of the degree of infiltration of the anal canal. Case report. AES was performed with the use of Bruel and Kjaer scanner type 3535 with an axial 10.0 MHz endoprobe. Examination was performed in decubitus position. Anal ultrasound allowed the exact assessment of the depth of infiltration of the anal wall by the tumour. Assessrnent of the perianal lymph nodes was also possible. Conclusions. AES became a routine examination in staging anal tumours. In patients with leukoplakia AES proved valuable in assessing the depth of invasion and deciding on the choice of treatment and prognosis.
Keywords: anus; Anus Neoplasms; Anus, novotvorbe; diagnostika; Leukoplakia; Levkoplakija; Middle Age; Srednja leta; Ultrasonography; ultrazvočna diagnostika